scikit‐maad: An open‐source and modular toolbox for quantitative soundscape analysis in Python - Ulloa, Juan Sebastián; Haupert, Sylvain; Latorre, Juan Felipe; Aubin, Thierry; Sueur, Jérôme (Methods in ecology and evolution, 2021)
Passive acoustic monitoring is increasingly being applied to terrestrial, marine and freshwater environments, providing cost‐efficient methods for surveying biodiversity. However, processing the avalanche of audio recordings remains challenging, and represents nowadays a major bottleneck that slows down its application in research and conservation. We present scikit‐maad, an open‐source Python package dedicated to the analysis of environmental audio recordings. This package was designed to (a) load and process digital audio, (b) segment and find regions of interest, (c) compute acoustic features and (d) estimate sound pressure levels. The package also provides field recordings and a comprehensive online documentation that includes practical examples with step‐by‐step instructions for beginners and advanced users. scikit‐maad opens the possibility to efficiently scan large audio datasets and easily integrate additional machine learning Python packages into the analysis, allowing to measure acoustic properties and identify key patterns in all kinds of soundscapes. To support reproducible research, the package is released under the BSD open‐source licence, which allows unrestricted redistribution for commercial and private use. This development will create synergies between the community of ecoacousticians, such as engineers, data scientists, ecologists, biologists and conservation practitioners, to explore and understand the processes underlying the acoustic diversity of ecological systems. Resumen El monitoreo acústico pasivo se está aplicando cada vez más en ambientes terrestres, marinos y de agua dulce, proporcionando métodos costo‐eficientes para estudiar la biodiversidad. Sin embargo, procesar la avalancha de grabaciones colectadas sigue siendo un desafío y representa hoy en día un importante cuello de botella que ralentiza su aplicación en la investigación y la conservación. Presentamos scikit‐maad, un paquete de Python de código abierto dedicado al análisis de grabaciones de audio ambientales. Este paquete fue diseñado para (1) cargar y procesar grabaciones de audio digital, (2) segmentar y encontrar regiones de interés, (3) calcular características acústicas y (4) estimar niveles de presión sonora. Integrado al paquete, proporcionamos muestras de grabaciones de campo y una documentación en línea que incluye ejemplos prácticos con instrucciones paso a paso para principiantes y usuarios avanzados. scikit‐maad abre la posibilidad de analizar de manera eficiente grandes conjuntos de datos de audio e integrar paquetes complementarios de Python de aprendizaje automático en el flujo de análisis, lo que permite medir las propiedades acústicas e identificar patrones clave en todo tipo de paisajes sonoros. Para apoyar la investigación reproducible, el paquete se publica bajo la licencia de código abierto BSD, que permite la redistribución sin restricciones para uso comercial y privado. Este desarrollo creará sinergias entre la comunidad de investigadores en ecoacústica, como ingenieros, científicos de datos, ecólogos, biólogos y profesionales en conservación, para explorar y comprender los procesos subyacentes que dan origen a la diversidad acústica de los sistemas ecológicos.